'Drink clean, safe water and/or other fluids through-out the day even if you do not feel thirsty': a food-based dietary guideline for the elderly in South Africa. (20th September 2021) - Mukherjee, Upasana; Napier, Carin; Oldewage-Theron, Wilna
Abstract : This review summarises information from available literature to support the dietary guideline 'Drink Clean, Safe Water and/or Other Fluids Through-Out the Day Even if You Do Not Feel Thirsty' set for the elderly of South Africa (SA). Water is essential for life and is necessary for important functions of the body like maintenance of tissue structure, blood volume regulation, temperature regulation and excretion of metabolites through kidneys. Though water is necessary for all, the elderly are especially at risk of dehydration due to altered hormonal activity and body functions that reduce their sensitivity to thirst (water intake) and urination (water excretion). Total body water is also reduced in the elderly, so they are unable to buffer the effects of water loss in the body. Therefore, water intake should be monitored properly in the elderly so that they can lead a happy and healthy life and reduce the economic burden due to hospitalisation caused by water imbalance or dehydration, which is common in the elderly. Two litres of water per day is generally considered adequate, but there is no consensus regarding the exact requirement for water as need varies due to climate and physical activity levels. The importance of water to maintain bodily functions and the risk of dehydration substantiate the need for a dietary guideline to address the importance of clean and safe water/fluid consumption regularly throughout the day among the elderly in SA.